Adapting to reality: Effect of Online Assessments as Compared to In‐Person Assessments. (20th December 2022) - Pallen, Vanessa; Rahmouni, Nesrine; Tissot, Cécile; Stevenson, Jenna; Stevenson, Alyssa; Poltronetti, Nina Margherita; Bezgin, Gleb; Lussier, Firoza Z; Therriault, Joseph; Kunach, Peter; Pascoal, Tharick; Servaes, Stijn; et al.
Abstract: Background: Neuropsychological evaluations are normally assessed in‐person by a trained psychometrician using a variety of tests representing several domains. The COVID‐19 pandemic has obliged medicine and research to switch to online assessment. However, minimal research has tested the reliability of conducting cognitive evaluations online versus in‐person. This study aims to explore the clinical utility of virtually assisted neuropsychological evaluations in a comparative analysis following the effects of the COVID‐19 pandemic. Method: 62 cognitively unimpaired (CU) individuals from the TRIAD cohort underwent baseline and follow‐up neuropsychological assessments which included the Boston Naming Test (Short Form), BORB‐Object Recognition Task, WASI‐II Matrix Reasoning, WAIS‐III Digit Span, D‐KEFS Category Fluency Tests, Rey Auditory Verbal Learning Test (RAVLT), and Free & Cued Selective Reminding Test (FCSRT) . Participants were considered CU when they obtained a CDR score of 0, MMSE ≥ 26, with negative amyloid‐β and tau statuses (global amyloid‐β [ 18 F]AZD4694 <1.55 SUVR and temporal meta‐ROI [ 18 F]MK6240 <1.24 SUVR). Participants were divided into two equally represented groups, both of which completed an in‐person baseline evaluation. 30 participants completed their follow‐up evaluation in‐person and 32 completed their evaluation virtually. A mixed linear regression model was used to assess the difference in the rate of change in scores between cohorts using age, sex, and years of education as covariates. Result: Follow‐up at‐home neuropsychological test results did not significantly differ from in‐person scores across all domains. Participant demographics are shown in table 1. The Boston Naming Test (Short Form), BORB‐Object Recognition Task, WASI‐II Matrix Reasoning, WAIS‐III Digit Span, D‐KEFS Category Fluency Tests, Rey Auditory Verbal Learning Test (RAVLT), and Free & Cued Selective Reminding Test (FCSRT) yielded p values of 0.47, 0.74, 0.17, 0.28, 0.13, 0.53, and 0.77, respectively. Conclusion: Scores from our battery were selected to represent the different cognitive domains. Based on our findings, there was no difference when individuals conducted in‐person versus online assessments. These results will allow for the geriatric community to receive the medical assistance they require without having to impose any inconveniences or unnecessary health risks. Additionally, virtual assessments will assist to increase contact for prospective participants which would otherwise not be possible in‐person.